Pengaruh Profesionalisme Auditor Dan Komitmen Organisasi Terhadap Kinerja Internal Auditor - Chairul Anwar; Tiya Agustina (Universitas Bandar Lampung (UBL), 2014)
This research aims to find out whether the auditor's professionalism and organizational commitment affect the performance of the internal auditor. The population in this research is the internal auditor at industrial enterprises in the province of Lampung, the data collected by sending a questionnaire to the internal auditor of the industrial enterprises in the province of Lampung. Questionnaire sent as many as 72, of the 72 deployed only 56 questionnaire questionnaire return and declared complete and eligible for further processing. The methods used to test each hypothesis is the Test T. The results of this research indicate that all hypotheses are built can be received, the results of this study support the H1, H2, and H3. This suggests that professionalism in a positive effect on the performance of the internal auditor, the Organization's commitment to a positive effect on the performance of the internal auditor, collectively the same professionalism and commitment to the Organization's positive effect on the performance of the internal auditor.